Application of MTT assay for probing metabolic activity in bacterial biofilm-forming cells on nanofibrous materials - Stindlova, Marta; Peroutka, Vaclav; Jencova, Vera; Havlickova, Kristyna; Lencova, Simona (Journal of microbiological methods, 2024)
The quantification of cellular metabolic activity via MTT assay has become a widespread practice in eukaryotic cell studies and is progressively extending to bacterial cell investigations. This study pioneers the application of MTT assay to evaluate the metabolic activity of biofilm-forming cells within bacterial biofilms on nanofibrous materials. The biofilm formation of Staphylococcus aureus and Escherichia coli on nanomaterials electrospun from polycaprolactone (PCL), polylactic acid (PLA), and polyamide (PA) was examined. Various parameters of the MTT assay were systematically investigated, including (i) the dissolution time of the formed formazan, (ii) the addition of glucose, and (iii) the optimal wavelength for spectrophotometric determination. Based on interim findings, a refined protocol suitable for application to nanofibrous materials was devised. We recommend 2 h of the dissolution, the application of glucose, and spectrophotometric measurement at 595 nm to obtain reliable data. Comparative analysis with the reference CFU counting protocol revealed similar trends for both tested bacteria and all tested nanomaterials. The proposed MTT protocol emerges as a suitable method for assessing the metabolic activity of bacterial biofilms on PCL, PLA, and PA nanofibrous materials.
Keywords: Polyesters; Spectrophotometry; thiazoly; Staphylococcus aureus; Glucose; Nylons; biofilmy; nylony; nanovlákna; polyestery; tetrazoliové soli; Escherichia coli; glukosa; spektrofotometrie; Biofilms; Nanofibers; Tetrazolium Salts; Thiazoles